Nietzsche’s Intellectual Integrity and Metaphysical Comfort - Ojimba, Anthony Chimankpam (Conatus - Journal of Philosophy, 2024)
This paper examines Nietzsche’s intellectual integrity, with a view to showing that despite his attempt to overcome metaphysics, using this concept, Nietzsche remains within the comfort of metaphysics. Intellectual integrity represents Nietzsche’s unique style of questioning and his critical method of analysing Western metaphysical foundations. It is a flexible and dialectic principle, which approaches the question of ‘being’ as a dynamic process of endless interpretations and becoming, instead of as a fixed essence or a metaphysical absolute. Attempts are made, in the paper, to examine the dynamics of Nietzsche’s intellectual integrity, as well as its intimate link with other key concepts in his philosophy. To achieve its goal, the paper adopts the method of historical hermeneutics and textual analysis.